PENGARUH KARAKTERISTIK AUDIT TERHADAP TAX AVOIDANCE - Nisrina Putri Madani (2021)
This study aims to determine the effect of audit characteristics which are divided into audit fees, tenure audits, and audit opinions on tax avoidance in consumer goods industry companies listed on the Indonesia Stock Exchange in the 2017-2019 period. This research is a type of quantitative research that uses secondary data in the form of company annual reports. This study used a sample of 96 companies. Techniques to analyze the data in this study using classical assumption test, regression model selection test, panel data regression, coefficient of determination hypothesis testing and partial hypothesis testing (T test). Based on the results of data analysis, it can be concluded that (1) audit fees has a significant negative effect on tax avoidance, (2) tenure audits has no effect on tax avoidance, (3) audit opinion has no effect on tax avoidance.